Analisis Pengaruh Rasio Likuiditas, Solvabilitas dan Rehabilitas Terhadap Kinerja Laporan Keuangan Bank Konvesional (Tahun 2017-2021) - Kusuma Wijaya (MAMEN: Jurnal Manajemen, 2022)
One of the factors of economic stability of a country is in the field of banking. A country with good banking management will stabilize the country's economy. Banking management is considered good, if one of the factors is regarding the performance of financial statements that are managed and presented correctly and appropriately. Liquidity ratio, solvency ratio and rentability ratio are ratios used to measure how well the banking financial statements are performing. The study aims to determine the effect of liquidity, solvency and rentability ratios on the performance of financial statements of conventional banks listed on the IDX in 2017-2021. Samples from 15 banks. The results of the study, partially Liquidity, Solvency and Profitability Ratios have a significant effect on Financial Performance, this is evidenced by the value of t count Liquidity (109.7), solvency (25,639) and rentability (7,979) always greater than t table (1,993). And simultaneously (together) Liquidity, Solvency and Profitability Ratios have a significant effect on financial performance of 15 banks listed on the Indonesia Stock Exchange, this is evidenced by the value of Fcount > Ftable (4310,310 > 2.73) and a significance value of 0,000 < 0.05.